Insect pollinators on Ananas comosus Linn. in pineapple cultivation hub at Tangkit Baru Village, Jambi Province: A preliminary study - Ratna, Yuni; Ristyadi, Dwi; Arifah, Windyna (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
The flowers of Ananas comosus, pineapple, are generally self-sterile which means seeds will only develop if cross-pollination occurs. Therefore, insect pollinators play a crucial role in fostering and preserving genetic diversity in pineapple plants. Our research aimed as a preliminary study to gain insight into the key pollinators that play a significant role in the pollination of A. comosus in Tangkit Baru village, a prominent pineapple cultivation hub in Jambi Province. Sampling was done in 20 sampling points, five times at five-day intervals. Sampling was carried out using yellow sticky traps, sweep net, and direct observation. All the collected insects were identified to species level, then species diversity and evenness were assessed using Shannon’s diversity index (H’) and Pielou’s evenness index (J’). A total of 1167 individuals, representing 31 distinct species of insect pollinators belonging to 14 families were found in our sampling sites. We found four dominant species that could potentially serve as the key pollinators of A. comosus in our sampling site, i.e. Dolichoderus thoracicus, Pygophora enigma, Pygophora respondens, and Anoplolepis gracilipes. The diversity and evenness of insect pollinators in the sampling site were at a moderate level, with Shannon’s diversity index (H’) value of 2.0785 and pielou’s evenness index (J’) value of 0.6053. Habitat enhancement measures are needed to preserve and improve the existing pollinator diversity and evenness in the agroecosystem.